2019
DOI: 10.25130/jtuh.26.3.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

Advice in English and Arabic television health programs

Abstract: This study deals with advising speech act from a polite point of view. Advising speech act implies that there is an expert who has knowledge of something and tries to share it with others for their own benefit .Since this study is concerned with health advice, it is very important to show the language used in health context which is medical language. The current study investigates the pieces of advice that are presented in TV health programmes 'The Doctors' and 'Green Apple'. This study aims at:(1) showing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several studies have been conducted to investigate the speech act of giving health advice in different contexts, including radio advice programs ( DeCapua and Dunham, 1993 ), TV health programs ( Ahmed and Ahmed, 2019 ), Twitter ( El-Dakhs, 2021 ), and online forums ( Morrow, 2006 ; Kouper, 2010 ; Locher, 2013 ; Pung, 2017 ; Bates, 2021 ). For example, in the context of radio advice programs, DeCapua and Dunham (1993) examined the patterns in American English used by speakers (adults) when requesting and giving advice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been conducted to investigate the speech act of giving health advice in different contexts, including radio advice programs ( DeCapua and Dunham, 1993 ), TV health programs ( Ahmed and Ahmed, 2019 ), Twitter ( El-Dakhs, 2021 ), and online forums ( Morrow, 2006 ; Kouper, 2010 ; Locher, 2013 ; Pung, 2017 ; Bates, 2021 ). For example, in the context of radio advice programs, DeCapua and Dunham (1993) examined the patterns in American English used by speakers (adults) when requesting and giving advice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is because the advice-seeker expects the request to be evident from the description of the problem. On the TV health programs, Ahmed and Ahmed (2019) examined the advice given in Arabic (Green Apple) and English (doctors) programs. The results showed that all pieces of advice in the two programs were used in polite expressions, which reflects the strong relationship between advising speech acts and politeness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation